Polarisation dependence of two-photon absorption generated by band-limited amplified spontaneous emission noise in silicon avalanche photodiodes - Donegan, John; Bradley, Louise; Kilper, Daniel (My University, 2011)
Two-photon absorption (TPA) generated by unpolarised band-limited amplified spontaneous emission (BL-ASE) noise is found to be within 5% of that generated by circularly polarised BL-ASE noise for silicon-based devices. A simple formula that describes the TPA generated by partially polarised BL-ASE noise as a function of material dichroism is given and verified experimentally.
PUBLISHED
Keywords: Two-photon absorption (TPA); Unpolarised band-limited amplified spontaneous emission (BL-ASE); Circularly polarised BL-ASE; Photonic integrated circuits; Optical-signal-to-noise-ratio (OSNR)